Analysis of The Implementation of Enterprise Resource Planning Systems (Applications and Product in Data Processing) in Improving Employee Training Management Effectiveness: a Case Study at Pt Kai (Persero) Daop III Cirebon - Tien Hindasah; Triyani Triyani (CV. Publikasi Indonesia, 2026)
This study aims to analyze the implementation of ERP SAP HR in improving the effectiveness of employee training management in the HR and General Division of DAOP III Cirebon. The study used a qualitative approach with purposive sampling techniques to select eight informants who were directly involved in the planning, implementation, and evaluation of training as well as users of SAP/RAILEO ERP. Data was collected through in-depth interviews, observations, and documentation, then analyzed using NVivo 12 software to identify patterns, themes, subthemes, and linkages between aspects of training management. The results show that SAP ERP supports administrative efficiency, data integration, participant monitoring, and data-driven decision-making. However, the effectiveness of training management is not optimal because there are still manual processes that cause delays in information and gaps between system data and field practice. The Training Center/Training Center has full authority to maintain the security and uniformity of national training, but the limited flexibility for DAOP III hinders responsiveness to local needs. Granting limited access to SAP TEM, reducing manual mechanisms, improving SAP modules, strengthening user capacity, and implementing system integrity dashboards are recommended to improve the effectiveness and efficiency of training management. Follow-up research is recommended to explore the long-term impact of ERP SAP on its competencies, performance, and integration with other HR development programs at PT KAI.